2018
DOI: 10.1007/s11325-018-1626-6
|View full text |Cite
|
Sign up to set email alerts
|

Depression score changes in response to sleep disordered breathing treatment with positive airway pressure in a large clinic-based cohort

Abstract: PAP therapy and adherence were associated with improvement in depressive symptom severity in this clinical cohort. Patients with lower socioeconomic status derived less therapeutic benefit, suggesting that they faced additional barriers to treatment effectiveness.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
2
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 33 publications
1
2
0
Order By: Relevance
“…Edwards et al (2015) also demonstrated that improving sleep quality led to a significant reduction in the number of people with sleep apnea meeting the clinical cutoff for depression as measured by the PHQ-9, with this proportion reducing from 74.6% to just 3.9% following intervention. Similar results have been demonstrated by others (Balcan et al 2019;Relia et al 2018). Since eveningness is associated with reduced sleep quality and duration, we propose that insomnia symptoms can partially explain the prevalence of poorer affective outcomes in E-types, rather than eveningness having an intrinsic detrimental effect on well-being.…”
supporting
confidence: 90%
“…Edwards et al (2015) also demonstrated that improving sleep quality led to a significant reduction in the number of people with sleep apnea meeting the clinical cutoff for depression as measured by the PHQ-9, with this proportion reducing from 74.6% to just 3.9% following intervention. Similar results have been demonstrated by others (Balcan et al 2019;Relia et al 2018). Since eveningness is associated with reduced sleep quality and duration, we propose that insomnia symptoms can partially explain the prevalence of poorer affective outcomes in E-types, rather than eveningness having an intrinsic detrimental effect on well-being.…”
supporting
confidence: 90%
“…Few previous studies have examined associations between depression and objectively monitored treatment usage (Gagnadoux et al, 2014;Habukawa et al, 2010;Relia et al, 2018), with some relying on patients' selfreported usage (Schwartz & Karatinos, 2007). In a recent large clinical cohort study, patients who were deemed "adherent" ( > 4 h use per night, for at least 70% of nights per week) showed a clinically significant improvement in Patient Health Questionnaire (PHQ-9) depressive symptoms (Relia et al, 2018). In contrast, Habukawa et al (2010) did not find any difference in CPAP hours of use between depression responders and non-responders.…”
Section: Discussionmentioning
confidence: 99%
“…17 A study of 1,981 patients with sleep-disordered breathing found improved PHQ-9 scores in patients compliant with CPAP therapy and a greater improvement in patients with a baseline PHQ-9 higher than 10 (moderate severity). 18 ■ METABOLIC SYNDROME OSA is associated with metabolic disorders, including metabolic syndrome, though the causality between these 2 conditions is yet to be illuminated. Metabolic syndrome is a term used when an individual has 3 or more of the following features or conditions:…”
Section: ■ Drowsy Drivingmentioning
confidence: 99%